ANGI-02. GENOME-WIDE shRNA SCREEN IDENTIFIES CANDIDATE GENES DRIVING GLIOBLASTOMA INVASION. (11th November 2019) - Schuster, Anne; Neirinckx, Virginie; Klein, Eliane; Nazarov, Petr V; Oudin, Anais; Muller, Arnaud; Azuaje, Fransisco; Herold-Mende, Christel; Klink, Barbara; Niclou, Simone
Abstract: BACKGROUND: A major hallmark of glioblastoma (GBM) is its invasive capacity, contributing to its aggressive behaviour. Invasive cells cannot be easily removed by surgery or irradiation and eventually result in lethal recurrence. A better understanding of the invasion process and the key molecular players underlying the invasive potential of GBM may lead to the identification of new therapeutic targets for GBM patients. MATERIAL AND METHODS: To identify candidate genes responsible for invasion, a genome-wide shRNA screen was performed in patient-derived GBM cultures. The most promising candidate was validated in in vitro invasion assays, ex vivo brain slice cultures and in vivo orthotopic xenografts in mice. Gene knockdown in invasive GBM cells was compared with overexpression in non-invasive cells. RNAseq of knockdown cells, along with the generation of deletion constructs were applied to uncover the mechanisms regulating invasion. RESULTS: A zinc-finger domain containing protein was identified as an invasion essential candidate gene. Knockdown of this gene confirmed a strong impact on invasion in highly invasive GBM cells. In contrast, gene overexpression switched non-invasive GBM cells to an invasive phenotype. Deletion of one or both zinc-finger motifs decreased invasion indicating that both are essential for regulating invasion. Mutation of the nuclear localisation signal resulted in retention of the protein in the cytoplasm and loss of the invasion phenotype demonstrating that the protein activity is required in the nucleus. Gene expression analyses revealed that invasion-related genes are significantly regulated by the candidate gene once it is localized in the nucleus. CONCLUSION: We identified a zinc-finger containing protein as a novel driver of GBM invasion, presumably through transcription factor activity resulting in the induction of an invasive transcriptional program. This protein and its downstream pathway may represent novel promising targets to overcome invasive capacities in GBM.